Keep it zesty : a celebration of Lebanese flavors & culture from Edy's Grocer - Massih, Edy (Harperwave, 2024)
Born in a small fishing village in Lebanon, Edy Massih grew up eating and cooking alongside his Teitas (grandmothers), Odette and Jacquo, who taught him the secrets to preparing delicious Lebanese food, including how to roll labneh balls and bind homemade kibbeh by hand. When Edy moved to the United States with his family at age ten, cooking soon became his solace, and from eighteen onward, Edy steadily built his career as a chef and caterer, specializing in these dishes and many others from his native land.Then Covid-19 struck, and Edy's dreams, like those of many other culinary professionals, were nearly derailed by the pandemic. But when his adopted Teita Maria decided to retire ownership of her beloved neighborhood deli, Edy knew what he had to do. In only a few short months, the new sign, Edy's Grocer, went up, and the Lemony Corner of Brooklyn was born.